Proses Rekrutmen dan Seleksi Tenaga Pendidik dan Kependidikan Dalam Meningkatkan Kualitas Pendidikan di SMPN 34 Surabaya - Chelsea, Rismananda; Putri Nabila, Ica; Trihantoyo, Syunu (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Today's society is very concerned about the quality of a school or educational institution, many educators are not linear with their educational experience so that they are lacking in mastering the concept of learning and the material to be delivered in the teaching and learning process. Every educational institution, especially in Senior High School, which has a very important role in tracing the success of students in the future, the hope of every school is to get quality, competent human resources, and be able to compete in the globalization era. This of course must be considered, especially in the recruitment and selection sistem for educators and education personnel. The purpose of this article is to find out the recruitment and selection sistem of teaching staff and education personnel in improving the quality of education at SMPN 34 Surabaya. The method used is observation in the form of interviews, namely getting information from sources and data from relevant references.